2020
DOI: 10.2486/indhealth.2019-0069
|View full text |Cite
|
Sign up to set email alerts
|

Plantar fasciitis in physicians and nurses: a nationwide population-based study

Abstract: Approval of the research protocol This study was strictly conducted according to the Declaration of Helsinki and approved by the Institutional Review Board at Chi-Mei Medical Center. Informed Consent Since the NHIRD contains de-identified information, informed consents from the participants are waived, which does not affect the rights and welfare of the participants. Registry and the Registration No. of the study/Trial N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…As compared to these area of interest, limited data is available concerning the prevalence of plantar fasciitis which is commonly associated with long working hours, prolong standing, prolong sitting and writing on black boards in the teaching profession. 6,14 In the current study, 46.7% of studied population was suffering from plantar fasciitis. Contrary to our findings higher percentages of plantar fasciitis was reported by recent study by Alqahtani et al that reported prevalence of 85.5% foot pain among the teacher.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…As compared to these area of interest, limited data is available concerning the prevalence of plantar fasciitis which is commonly associated with long working hours, prolong standing, prolong sitting and writing on black boards in the teaching profession. 6,14 In the current study, 46.7% of studied population was suffering from plantar fasciitis. Contrary to our findings higher percentages of plantar fasciitis was reported by recent study by Alqahtani et al that reported prevalence of 85.5% foot pain among the teacher.…”
Section: Discussionmentioning
confidence: 64%
“…12 Unilateral plantar heel pain, more severe when person walks after awaking in morning or prolonged sitting are the characteristic features for PF. 6 PFPS also includes visual analogue scale (VAS) to assess intensity of pain. The VAS scores pain was rating the pain on a scale of 1 to 100 points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…También afecta a un 10 % de los corredores y es común en trabajadores y atletas, los cuales, en las actividades que realizan, tienen un gran impacto en el pie 3 . La FP es causada por factores que producen una sobrecarga en la inserción de la fascia plantar del calcáneo causando microrroturas de esta 6,7 .…”
Section: Introductionunclassified
“…These factors would create pathologic burden over calcaneal insertion of plantar fascia, which may further cause microtears in the fascia that may in the end lead to perifascial oedema and also increased heel pad thickness ensuing in interference of the normal biomechanics of the foot and eventually would lead to decrease in the competence of force absorption. This decrease in force absorption would therefore lead to overstressing of plantar fascia and increase the degenerative changes [7,8,9]. People with plantar fasciitis may present with heel pain with their first steps in the morning, or after long periods of sitting, and also elicit a response of sharp pain with palpation of the medial plantar calcaneal region [10].…”
mentioning
confidence: 99%